CD63-mediated cloaking of VEGF in small extracellular vesicles contributes to anti-VEGF therapy resistance - Ma, Shaolin; Mangala, Lingegowda S.; Hu, Wen; Bayaktar, Emine; Yokoi, Akira; Hu, Wei; Pradeep, Sunila; Lee, Sanghoon; Piehowski, Paul D.; Villar-Prados, Alejandro; Wu, Sherry Y.; McGuire, Michael H.; et al. (Cell reports (Cambridge), 2021)
Despite wide use of anti-vascular endothelial growth factor (VEGF) therapy for many solid cancers, most individuals become resistant to this therapy, leading to disease progression. Therefore, new biomarkers and strategies for blocking adaptive resistance of cancer to anti-VEGF therapy are needed. As described here, we demonstrate that cancer-derived small extracellular vesicles package increasing quantities of VEGF and other factors in response to anti-VEGF therapy. The packaging process of VEGF into small extracellular vesicles (EVs) is mediated by the tetraspanin CD63. Furthermore, small EV-VEGF (eVEGF) is not accessible to anti-VEGF antibodies and can trigger intracrine VEGF signaling in endothelial cells. eVEGF promotes angiogenesis and enhances tumor growth despite bevacizumab treatment. These data demonstrate a mechanism where VEGF is partitioned into small EVs and promotes tumor angiogenesis and progression. These findings have clinical implications for biomarkers and therapeutic strategies for ovarian cancer. [Display omitted] •Cancer cells package increasing amounts of VEGF in small EVs with anti-VEGF therapy•VEGF packaging into small EVs is mediated by the tetraspanin CD63•Anti-VEGF antibodies failed to recognize small EV-VEGF (eVEGF)•eVEGF triggers intracrine VEGF signaling and promotes angiogenesis Ma et.al report that cancer-cell-derived small EVs contain increasing amounts of VEGF (eVEGF) and contribute to resistance to anti-VEGF therapy (AVT). CD63 is a potential mediator that regulates packaging of VEGF into small EVs. eVEGF can trigger intracrine VEGF signaling in endothelial cells and promote angiogenesis despite AVT.